Effects of Continuous Positive Airway Pressure on the Degree of Sleepiness, Functional Quality of Sleep, and Electrophysiological Hearing Responses in Individuals with Obstructive Sleep Apnea - Farber, Marisa Mizrahi; Silva, Liliane Aparecida Fagundes; Lorenzi-Filho, Geraldo; Matas, Carla Gentile (Sleep Science, 2025)
Obstructive sleep apnea (OSA) affects nerve impulse transmission in the auditory pathway due to oxygen supply. Continuous positive airway pressure (CPAP) therapy improves oxygen levels, potentially alleviating sleepiness and enhancing central auditory pathway function.To longitudinally evaluate the effect of CPAP on the degree of sleepiness, functional quality of sleep, and electrophysiological hearing responses of the central auditory pathways of patients with moderate to severe OSA.There were 31 adults (21 men and 10 women), aged 20 to 70 years, of which 18 were from the group with and 13 from the one without CPAP. All patients underwent three assessments: the first one performed immediately after CPAP prescription; the second, 3 months later; and the third, 6 months after the initial assessment. The Epworth Sleepiness Scale (ESS), the Functional Outcomes of Sleep Questionnaire-10 (FOSQ-10), auditory brainstem response (ABR), and long-latency auditory evoked potentials (LLAEP) were used for these assessments.The ESS did not detect any changes in excessive daytime sleepiness levels and the FOSQ-10 showed no improvement in either group. Analysis from ABR revealed a high proportion of altered results in both groups at the three assessment times. During the LLAEP, it was observed that the CPAP group exhibited reduced P2 latencies compared with the non-CPAP group in the second assessment. However, this improvement was not sustained in the subsequent assessment, possibly attributed to OSA-induced damage.Treatment with CPAP for 6 months did not improve the degree of sleepiness, functional quality of sleep, or electrophysiological response of hearing, demonstrating that OSA can irreversibly harm the individual.
Keywords: obstructive sleep apnea; continuous positive airway pressure; sleepiness; sleep quality; evoked potentials auditory